Cell Cycle, Filament Growth and Synchronized Cell Division in Multicellular Cable Bacteria - Geerlings, Nicole M. J.; Geelhoed, Jeanine S.; Vasquez-Cardenas, Diana; Kienhuis, Michiel V. M.; Hidalgo-Martinez, Silvia; Boschker, Henricus T. S.; Middelburg, Jack J.; Meysman, Filip J. R.; Polerecky, Lubos (Frontiers in Microbiology, 2021)
Cable bacteria are multicellular, Gram-negative filamentous bacteria that display a unique division of metabolic labor between cells. Cells in deeper sediment layers are oxidizing sulfide, while cells in the surface layers of the sediment are reducing oxygen. The electrical coupling of these two redox half reactions is ensured via long-distance electron transport through a network of conductive fibers that run in the shared cell envelope of the centimeter-long filament. Here we investigate how this unique electrogenic metabolism is linked to filament growth and cell division. Combining dual-label stable isotope probing (13C and 15N), nanoscale secondary ion mass spectrometry, fluorescence microscopy and genome analysis, we find that the cell cycle of cable bacteria cells is highly comparable to that of other, single-celled Gram-negative bacteria. However, the timing of cell growth and division appears to be tightly and uniquely controlled by long-distance electron transport, as cell division within an individual filament shows a remarkable synchronicity that extends over a millimeter length scale. To explain this, we propose the “oxygen pacemaker” model in which a filament only grows when performing long-distance transport, and the latter is only possible when a filament has access to oxygen so it can discharge electrons from its internal electrical network.